The Influence of Regional Financial Independence and Population Size on Regional Production Capacity and Community Welfare in West Kalimantan Province - Desmi Sutami; Rosyadi Rosyadi; Erni Panca Kurniasih (Jurnal Indonesia Sosial Sains, 2025)
This study examines the influence of regional financial independence and population quantity on regional production capacity and community welfare in West Kalimantan Province. Using a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS), panel data from 14 districts/cities during the 2015–2024 period were analyzed. Regional financial independence was measured through the degree of fiscal decentralization, degree of regional dependence, and ratio of fiscal independence. Population quantity was assessed using population density, labor force participation rate, and dependency ratio. Regional production capacity was represented by Gross Regional Domestic Product (GDP), while community welfare was measured by the Human Development Index (HDI). The results indicate that regional financial independence significantly affects both regional production capacity (t-stat = 2.163, p = 0.031) and community welfare (t-stat = 13.019, p = 0.000). Population quantity also shows significant effects on production capacity (t-stat = 2.989, p = 0.003) and welfare (t-stat = 3.923, p = 0.000). Furthermore, regional production capacity significantly influences community welfare (t-stat = 2.154, p = 0.031). The mediation analysis reveals that production capacity successfully mediates the relationship between population quantity and community welfare (t-stat = 2.668, p = 0.008), but does not mediate the relationship between regional financial independence and welfare (t-stat = 1.738, p = 0.082). The model demonstrates strong predictive relevance with an R-square value of 81.0% for community welfare and a Q-square value of 89.9%. These findings emphasize that strengthening fiscal independence and optimizing demographic potential through enhanced production capacity are crucial strategies for improving community welfare in West Kalimantan Province.